Analisis Dampak Sosial Ekonomi Alih Fungsi Lahan Pertanian Menggunakan Interpretative Structural Modeling (ISM) di Kota Parepare - Edi Kurniawan; Rahmi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The continuous conversion of agricultural land into non-agricultural uses in Parepare City has substantially reduced productive farmland and generated various socio-economic impacts on local communities. This phenomenon is a critical issue as it threatens local food security, alters employment structures, and affects household welfare, particularly among farmers. This study aims to: (1) analyze land-use changes resulting from agricultural land conversion, (2) identify the economic impacts arising from the conversion, (3) examine its effects on the community’s economic structure, and (4) explain the social consequences that emerge as a result of these changes. A qualitative descriptive approach was employed, supported by Interpretative Structural Modeling (ISM) to map the relationships and levels of influence among the affected socio-economic factors. The findings indicate that the most influential factors driving socio-economic change are access to infrastructure, natural resources, and education. Economically, land conversion has led to shifts in livelihoods, changes in income levels, and a decline in household purchasing power among farmers. Socially, community cooperation has weakened, and changes in social structures have become evident. In conclusion, agricultural land conversion has significant implications for the socio-economic conditions of communities in Parepare City. This study highlights the need for sustainable spatial planning policies, improved non-agricultural skills development, and strengthened economic and educational literacy to support community adaptation to ongoing land-use changes. The continuous conversion of agricultural land into non-agricultural uses in Parepare City has substantially reduced productive farmland and generated various socio-economic impacts on local communities. This phenomenon is a critical issue as it threatens local food security, alters employment structures, and affects household welfare, particularly among farmers. This study aims to: (1) analyze land-use changes resulting from agricultural land conversion, (2) identify the economic impacts arising from the conversion, (3) examine its effects on the community’s economic structure, and (4) explain the social consequences that emerge as a result of these changes. A qualitative descriptive approach was employed, supported by Interpretative Structural Modeling (ISM) to map the relationships and levels of influence among the affected socio-economic factors. The findings indicate that the most influential factors driving socio-economic change are access to infrastructure, natural resources, and education. Economically, land conversion has led to shifts in livelihoods, changes in income levels, and a decline in household purchasing power among farmers. Socially, community cooperation has weakened, and changes in social structures have become evident. In conclusion, agricultural land conversion has significant implications for the socio-economic conditions of communities in Parepare City. This study highlights the need for sustainable spatial planning policies, improved non-agricultural skills development, and strengthened economic and educational literacy to support community adaptation to ongoing land-use changes.